The Effect of Technology Utilization in Learning on Learning Motivation of Grade 11 PPLG Students of State Vocational Schools in Surakarta - Pratama, Septian Nur Fajar; Basori, Basori; Kurniasari, Kurniasari (Indonesian journal of informatics education, 2024)
Education is a field that continues to develop along with technological advances. One important aspect of learning is student motivation because high motivation can improve learning outcomes. The utilization of information technology is very relevant, especially in State Vocational Schools in Surakarta which focus on the field of software and game development. Learning activities and the relevance of the material are the two key aspects that affect students' motivation. High meaningfulness of subject matter can encourage students to learn because students feel that the material studied is relevant to their lives. Interesting and fun learning activities can also increase student motivation to learn. Information technology can be a powerful tool to increase student motivation. To help kids study more efficiently and reach their full potential, specially created technology may be adapted to each student's needs and skills. In this study, grade XI students at State Vocational Schools in Surakarta will have their motivation to learn about the impact of using information technology in the classroom examined. This research uses qualitative methods to explore this. Through qualitative data analysis with interview and observation methods, it is expected to find a comprehensive picture of the extent of the influence of information technology utilization on learning motivation.